Innovation of Madrasah Curriculum Based on Boarding School as An Effort to Develop Islamic Religious Education Subject Learning at Ma’ahid Aliyah Madrasah Kudus - Shifa, Tafrihatush; Az Zafi, Ashif (The Magister of Islamic Education IAIN Pontianak, 2025)
Curriculum innovation is a strategic necessity in Islamic education, especially in madrasahs, to address contemporary challenges while preserving the religious values that form the core of Islamic educational identity. This study aims to analyze the form and implementation of pesantren-based curriculum innovation in Islamic Religious Education (PAI) learning at Madrasah Aliyah Ma’ahid Kudus. The research employed a qualitative field study approach. Data were collected through in-depth interviews with the head of the madrasah, the vice principal of curriculum, PAI teachers, boarding school managers, and students; along with classroom observations, field preaching (PDL) activities, and supporting documentation. The results reveal that MA Ma’ahid has developed a curriculum innovation by integrating the national Merdeka Curriculum with the pesantren curriculum rooted in classical Islamic texts (kitab kuning). This integration is reflected in PAI learning through traditional pesantren methods such as sorogan, bandongan, memorization, and halaqah. Additionally, field preaching practice (PDL) is implemented as a co-curricular activity to enhance students’ character and social competence. Through PDL, students are directly involved in teaching, preaching, and engaging with the community through activities like sermons, competitions, and worship practice. The novelty of this study lies in its contextually integrated curriculum model based on local wisdom, combining cognitive and spiritual aspects while fostering students' practical, leadership, and communication skills. This research offers significant value by providing an alternative model for Islamic Religious Education that is relevant, applicable, and sustainable. The findings are expected to serve as a reference for other pesantren-based madrasahs seeking to develop holistic curricula that prepare students to be religious, independent, socially engaged, and globally competitive individuals in the face of modern challenges.